2017
DOI: 10.1136/tobaccocontrol-2017-053691
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between trying an electronic cigarette and subsequent cigarette experimentation in Scottish adolescents: a cohort study

Abstract: BackgroundThis study examines whether young never smokers in Scotland, UK, who have tried an e-cigarette are more likely than those who have not, to try a cigarette during the following year.MethodsProspective cohort survey conducted in four high schools in Scotland, UK during February/March 2015 (n=3807) with follow-up 1 year later. All pupils (age 11–18) were surveyed. Response rates were high in both years (87% in 2015) and 2680/3807 (70.4%) of the original cohort completed the follow-up survey. Analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
135
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(149 citation statements)
references
References 36 publications
(30 reference statements)
6
135
1
2
Order By: Relevance
“…Using parameters from the CASP tool for cohort studies, the included studies were generally of good quality ( Table 1) while risk of bias was mainly low ( Table 2). Over all of the eight included studies 20,[42][43][44][45][46][47][48] there were a total of 73076 adolescents aged 10-19 years ( Table 3). Five of the studies used a crosssectional survey design 20,45-48 while three [42][43][44] were longitudinal (prospective) designs and were able to be included in a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using parameters from the CASP tool for cohort studies, the included studies were generally of good quality ( Table 1) while risk of bias was mainly low ( Table 2). Over all of the eight included studies 20,[42][43][44][45][46][47][48] there were a total of 73076 adolescents aged 10-19 years ( Table 3). Five of the studies used a crosssectional survey design 20,45-48 while three [42][43][44] were longitudinal (prospective) designs and were able to be included in a meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Smoking initiation does not mean regular use, however it can be taken as a potential starting point that could easily progress to regular use of a substance 49 . Three longitudinal studies [42][43][44] Almost half of those who had tried smoking had tried an e-cigarette. 42.8% of young people who had used e-cigarettes reported that they had never smoked tobacco.…”
Section: Smoking Initiationmentioning
confidence: 99%
“…22 Using principal component analysis, FAS scores were transformed into a single-dimensional score which was then divided into tertiles of high, medium and low FAS. 23 Smoking status was measured with the question 'Have you ever smoked cigarettes or hand-rolled cigarettes (roll-ups), even if it is just one or two puffs?' and among those answering 'yes', those who indicated 'I currently smoke cigarettes or hand-rolled cigarettes (roll-ups)' were considered smokers.…”
Section: Covariatesmentioning
confidence: 99%
“…Conner et al 1 and Best et al 2 report the results of two longitudinal studies of teenagers in the UK that examined the relationship between vaping an e-cigarette and smoking a cigarette. Similar to studies conducted in the USA,3 4 they both report an association between experimentation with vaping and subsequent experimentation with smoking.…”
mentioning
confidence: 99%
“…The baseline waves of these longitudinal studies were conducted in locations and at times when there were no age restrictions on sales of vaping products 2. In such a regulatory context, it is not surprising that young people may have tried the product with less restrictions first 5.…”
mentioning
confidence: 99%